2012
DOI: 10.1002/art.34650
|View full text |Cite
|
Sign up to set email alerts
|

Impact of genetic ancestry and sociodemographic status on the clinical expression of systemic lupus erythematosus in American Indian–European populations

Abstract: Objective Amerindian-Europeans, Asians and African-Americans have an excess morbidity from SLE and higher prevalence of lupus nephritis than Caucasians. The aim of this study was to analyze the relationship between genetic ancestry and socio-demographic characteristics and clinical features in a large cohort of Amerindian-European SLE patients. Methods A total of 2116 SLE patients of Amerindian-European origin and 4001 SLE patients of European descent with clinical data were used in the study. Genotyping of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 36 publications
3
68
1
Order By: Relevance
“…AA ancestral background has been associated with increased incidence and severity of disease, and increased levels of autoantibodies and type I IFN [1][13, 39, 43]. In the present study, we saw a greater number of DEGs in AA patients as compared to EA patients in each cell type.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…AA ancestral background has been associated with increased incidence and severity of disease, and increased levels of autoantibodies and type I IFN [1][13, 39, 43]. In the present study, we saw a greater number of DEGs in AA patients as compared to EA patients in each cell type.…”
Section: Discussionsupporting
confidence: 60%
“…Clinically, SLE patients from different ancestral backgrounds manifest differently. For example, Amerindian genetic ancestry is associated with earlier onset of SLE and an increased risk of developing renal involvement as compared to European-American ancestry [1]. Distinct patterns of genetic association with SLE exist between world populations, with some genetic factors being associated in one background but not the other [2-6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sanchez et al found more mouth ulcers, malar rashes, serositis, arthritis, neurological impairment and discoid lupus erythematosus (DLE) in patients of European descent compared with American-Indians; however, these are weak correlations which often disappear with multivariate analysis. 3 In a large multiethnic cohort of SLE, DLE, arthritis and terminal renal failure were negatively associated with Hispanic, but positively associated with African-American populations. 6 Another study demonstrated a positive association of antiphospholipid antibodies in 'Aboriginal' Canadians with SLE, compared with persons of Asian or European descent.…”
Section: Lupus Erythematosusmentioning
confidence: 96%
“…The recent use of genetic tools such as ancestry informative markers now enables a more objective assessment of ethnicity, even in persons of mixed ancestral backgrounds. 3 Studies have also demonstrated that the prognosis of SLE is worse in nonwhite persons, in whom there is a younger age at onset of their disease, as well as a higher frequency of severe renal disease. [1][2][3][4][5] These observations may be due to 'protective factors' associated with European ancestry or may indicate the presence of specific risk factors associated with other ethnic groups.…”
Section: Lupus Erythematosusmentioning
confidence: 99%
“…The incidence and prevalence of SLE is higher in non-European ancestry, especially in African ancestry. The severity of SLE also varies among the ethnic groups, being more severe in non-European populations [24]. Supporting a genetic contribution to disease, monozygotic twins are much more likely to be concordant for SLE than dizygotic twins (concordance rate 24% and 2%, respectively) [5].…”
Section: Introductionmentioning
confidence: 99%